FORMS OF ADDRESS «YOU/YOU» IN UZBEK AND GERMAN (Scientific journal of the Fergana State University, 2023)
In this article, the forms of address "you/you (polite form)" in Uzbek and German speech etiquette, various examples of situations of their use from works of art and their significance in the life of representatives of two nationalities, "siezen" (addressing you), "duzen" (addressing you in polite form) features of when and in what situations it is used, including two different situations in the speech of two peoples when referring to parents, siblings, relatives and friends in the family, what forms of address are used in official circles, to communicants of the two peoples The use of such forms of address as "du-you" and "Sie-You", expressing respect and closeness in everyday life, as well as their common, similar and different aspects, is revealed.